2015
DOI: 10.1039/c4cp05030d
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and thermal stability of aluminum-based nanoparticles prepared from the rapid cooling of nanodroplets: effect of iron addition

Abstract: Despite an intensive investigation on bimetallic nanoparticles, little attention has been paid to their amorphization in the past few decades. The study of amorphization on a nanoscale is of considerable significance for the preparation of amorphous nanoparticles and bulk metallic glass. Herein, we pursue the amorphization process of Al-based nanoparticles with classic molecular dynamics simulations and local structural analysis techniques. By a comparative study of the amorphization of pure Al and Fe-doped Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In the present work, MAEAM potential was adopted to describe atomic bonding in Cu–Pt NAs because of their underpinnings in quantum mechanics, mathematic simplicity, and extendibility to alloy materials. The original EAM potential, , the modified one (MEAM), ,, and our MAEAM one have already been successfully applied for the study of bulk, surface, and nanoparticles of metals and alloys through incorporating many-body interactions. In short, for a monometallic system, the original EAM represents the energy per atom as a sum of the pair interaction energy and the embedding energy .…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, MAEAM potential was adopted to describe atomic bonding in Cu–Pt NAs because of their underpinnings in quantum mechanics, mathematic simplicity, and extendibility to alloy materials. The original EAM potential, , the modified one (MEAM), ,, and our MAEAM one have already been successfully applied for the study of bulk, surface, and nanoparticles of metals and alloys through incorporating many-body interactions. In short, for a monometallic system, the original EAM represents the energy per atom as a sum of the pair interaction energy and the embedding energy .…”
Section: Model and Methodsmentioning
confidence: 99%
“…In this perspective, we performed MC simulations with the modified analytical embedded atom method (MAEAM) potential to unravel the roles of surface segregation and chemical ordering in determining the thermodynamically stable structure of Cu–Pt NAs. Parameters such as alloy composition, particle shape and size, and system temperature were correlated with surface Cu composition and the chemical ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the amorphous structure could be only obtained by the fast-cooling process, otherwise crystalline phase during the common-cooling procedure. Generally, crystalline energy can be suddenly dropped caused by a rapid cooling process, which inhibits the rearrangement of the atoms and results in the formation of a noncrystalline structure inherited from the molten state, [38,39] thus manifesting that this amorphization approach is controllable and facile. Furthermore, during the high-temperature sulfidation, the MOF would transform into the coating carbon and in situ wrap on the surface of GeS 2 , which could improve the conductivity of the entire electrode.…”
Section: Research Articlementioning
confidence: 99%
“…33 In the case of iron aluminide NPs an additional fundamental problem of such a synthetic approach is the formation of stable iron-centered clusters even at low Fe concentration, which suppresses the nucleation process and thus, the growth of crystalline particles. 34 Therefore, even larger concentrations of Fe led to amorphous nanomaterials, which may be interesting in terms of catalysis but are much more difficult to analyze. 34 Dutta et al and Pithawalla et al, who described the wet-chemical synthesis of FeAl or Fe 3 AlC 0.5 nanoparticles by reducing anhydrous iron(II) chloride with lithium aluminum hydride, showed that a subsequent thermal treatment at temperatures of over 500 C is required for the crystallization of the initial amorphous material.…”
Section: Schütte Et Al Reported the Synthesis Of Ni/gamentioning
confidence: 99%
“…34 Therefore, even larger concentrations of Fe led to amorphous nanomaterials, which may be interesting in terms of catalysis but are much more difficult to analyze. 34 Dutta et al and Pithawalla et al, who described the wet-chemical synthesis of FeAl or Fe 3 AlC 0.5 nanoparticles by reducing anhydrous iron(II) chloride with lithium aluminum hydride, showed that a subsequent thermal treatment at temperatures of over 500 C is required for the crystallization of the initial amorphous material. 35,36 Therefore, ball-milling, as a top-down process, is the most reported way for the preparation of Fe/Al NPs.…”
Section: Schütte Et Al Reported the Synthesis Of Ni/gamentioning
confidence: 99%